Sample Sequence Analysis Uncovers Recurrent Horizontal Transfers of Transposable Elements among Grasses. (8th May 2021) - Park, Minkyu; Christin, Pascal-Antoine; Bennetzen, Jeffrey L
Abstract: Limited genome resources are a bottleneck in the study of horizontal transfer (HT) of DNA in plants. To solve this issue, we tested the usefulness of low-depth sequencing data generated from 19 previously uncharacterized panicoid grasses for HT investigation. We initially searched for horizontally transferred LTR-retrotransposons by comparing the 19 sample sequences to 115 angiosperm genome sequences. Frequent HTs of LTR-retrotransposons were identified solely between panicoids and rice ( Oryza sativa ). We consequently focused on additional Oryza species and conducted a nontargeted investigation of HT involving the panicoid genus Echinochloa, which showed the most HTs in the first set of analyses. The comparison of nine Echinochloa samples and ten Oryza species identified recurrent HTs of diverse transposable element (TE) types at different points in Oryza history, but no confirmed cases of HT for sequences other than TEs. One case of HT was observed from one Echinochloa species into one Oryza species with overlapping geographic distributions. Variation among species and data sets highlights difficulties in identifying all HT, but our investigations showed that sample sequence analyses can reveal the importance of HT for the diversification of the TE repertoire of plants.